2021
DOI: 10.1038/s41380-020-01006-9
|View full text |Cite|
|
Sign up to set email alerts
|

Investigating rare pathogenic/likely pathogenic exonic variation in bipolar disorder

Abstract: Bipolar disorder (BD) is a serious mental illness with substantial common variant heritability. However, the role of rare coding variation in BD is not well established. We examined the protein-coding (exonic) sequences of 3,987 unrelated individuals with BD and 5,322 controls of predominantly European ancestry across four cohorts from the Bipolar Sequencing Consortium (BSC). We assessed the burden of rare, protein-altering, single nucleotide variants classified as pathogenic or likely pathogenic (P-LP) both e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…The overlap in BD, however, remains uncertain. The BSC exome-dataset examined 3,987 BD cases ( 14 ), finding suggestive enrichment in 165 genes implicated in BD GWAS (OR = 1.9, P = 6.0 × 10 −4 ), but this finding did not replicate in the current sample (OR = 0.9, P = 0.40). Given that prior evidence of common and rare gene overlap in schizophrenia was quite modest ( 16, 17, 29 ), as sample sizes increase for both common and rare variation analyses in BD, we do expect to see a slow but steady convergence in much the same manner.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The overlap in BD, however, remains uncertain. The BSC exome-dataset examined 3,987 BD cases ( 14 ), finding suggestive enrichment in 165 genes implicated in BD GWAS (OR = 1.9, P = 6.0 × 10 −4 ), but this finding did not replicate in the current sample (OR = 0.9, P = 0.40). Given that prior evidence of common and rare gene overlap in schizophrenia was quite modest ( 16, 17, 29 ), as sample sizes increase for both common and rare variation analyses in BD, we do expect to see a slow but steady convergence in much the same manner.…”
Section: Discussionmentioning
confidence: 75%
“…To test whether bipolar cases carry an excess of damaging coding variants, we analyzed exome-wide burden relative to controls using a logistic regression model controlling for principal components, sex, and overall coding burden (supplementary materials: exome-wide burden analyses). Drawing from previous exome sequencing studies of psychiatric disease ( 14, 16, 17 ), we restricted our attention to variants with minor allele count (MAC) ≤ 5 across the entirety of the dataset, corresponding to MAF ≤ 0.01%. We annotated variants using the Ensembl Variant Effect Predictor (VEP) ( 18 ) version 95 with the loftee plugin, and assigned variants to classes of variation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Familybased studies in SCZ [7][8][9] , BD [10][11][12][13] and OCD 14 have identified multiple rare de novo and loss of function variations relevant to the biology of each syndrome. Similarly, case-control association studies in SCZ 4,5 and BD 15,16 have also identified the contribution of rare variants of large effect, advancing the current understanding of genetic architecture of these syndromes. An overview of recent findings from family based and case-control sequencing studies in SMI is presented in the supplement S1.…”
Section: Introductionmentioning
confidence: 98%
“…Another recent GWAS reported 64 important loci ( 6 ). Recent sequencing studies have suggested possible roles for rare mutations, although the findings are equivocal ( 7 ), as is the role of copy number variation ( 8 ). Some rare mutations may cause somatic diseases that confer a risk of bipolar disorder ( 1 , 9–11 ).…”
Section: Introductionmentioning
confidence: 99%